Perancangan dan Pengembangan Websıte Company Profıle dan Sıstem Pemesanan Melaluı Chat Pada Mını Brown Cheese Cake - Syaeful Anas Aklani; Derwin Galen (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2021)
The aim of this community service program is to increase way to promote, information, and buy Mini Brown Cheese Cake products by making a company profile website that can also order by using chat. The partners in this program are Mini Brown Cheese Cake, which is a cake shop that mainly sells cheese cake as it’s main product. This cake shop has been founded in 2016 and is located at Ruko Mahkota Raya Blok C No 06, Teluk Tering, Batam City. Besides the shop at Batam City it also has branches in Pekanbaru City, Pontianak City, and Banjarmasin City. The method used in to develop this company profile website is SDLC (Software Development Life Cycle) Method. This study results show that this website can help reaching new audiences and can also help with the legitimacy of a company.